Establishment Stage Competition between Exotic Crimson Fountaingrass (Pennisetum setaceum, C4) and Native Purple Needlegrass (Stipa pulchra, C3). (June 2015) - Sweet, Lynn C.; Holt, Jodie S.
Abstract : Southern California grasslands have largely been type-converted to dominance by exotic annual grasses, leading to displacement of many native grass and forb species. Crimson fountaingrass, Pennisetum setaceum, an exotic perennial C4 species and a relatively new invader to California, is expanding to areas currently occupied by purple needlegrass, Stipa pulchra, a C3 native. We predicted that fountaingrass seedlings might withstand cool season competition in California's Mediterranean-type climate and establish in Stipa pulchra grasslands due to less competition during the warm, dry summer season, and that interactions might be influenced by density. A field experiment was conducted to examine competitive interactions of the two species from the cool winter season to the warm summer season. As predicted, Stipa produced greater aboveground biomass in the cool season and showed strong intraspecific competition, as well as interspecific suppression of Pennisetum growth, whereas Pennisetum showed no suppression of Stipa . In the warm season, Stipa showed relatively less suppression of Pennisetum, erasing significant differences, and Pennisetum showed increased growth. Results of this study show that C3 Stipa can suppress initial growth of C4 Pennisetum in the cool season, but in warmer months, Pennisetum can overcome this initial suppression at both low and high densities, even within a Mediterranean-type climate with little to no summer rainfall. Thus, in southern California, temporal niche partitioning due to photosynthetic pathway in these two species can allow Pennisetum invasion. Given the similarity in life history and growth form of Stipa and Pennisetum, few options exist for controlling Pennisetum in habitats where Stipa occurs. In these cases, restoration plantings of desirable species are essential in order to reestablish competitive vegetation that will be more resistant to invasion.